Person with TBI, Key HealthTeam Member; Strategies toward Recovery (Global Journal of Medical Research, 2014)
A Traumatic Brain Injury (TBI) may result in brief, moderate, or lifelong physical, emotional, cognitive, behavioral, social and employment difficulties, extended unconsciousness, permanent disabilities, or death. The annual TBI incidence in the United States of 1.7 million people or more and the estimated 5.3 million people with TBI dwelling in the U.S. contribute to TBI being a grave public health issue. While the physician is typically considered the point person directing the medical care for an acute TBI, the key member of the health team should be the person with the TBI along with a family support person. A comprehensive approach to recovery should include early referrals to many other types of health professionals such as neurologists and other physician specialists, physical therapists, psychologists, speech therapists, etc. for early intervention and avoiding delays in healing that may result from subtle problems, cognitive dysfunction, depression, or vision and other sensory system deficits.